Pola Assesment Dalam Kebijakan Merdeka Belajar Menurut Perpektif Pendidikan Islam - Hadini, Hadini; Imamuddin, M. Imamuddin; saiful, saiful; Realita, Realita (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2023)
The step to implement the "Merdeka Belajar" policy taken by the Minister of Education is an effort to lift the quality of Indonesian education which is far behind among other countries, its existence is also expected to be able to accelerate competition in the era of information and Industry 4.0. which relies on the power of technology and the rapid digitisation of information. The birth of this policy has certainly given birth to greater implications in the education system in Indonesia. One of the impacts of the implementation of this policy is the change in the assessment system in educational institutions, where the form of assessment has its own characteristics that are different from the previous assessment system. To find the form and characteristics of the assessment system in the policy, this research tries to explore using the library research method. In this case, researchers conducted a search by analysing various literatures in the form of books, research results, and journals, both national and international, related to the assessment system in the "Merdeka Belajar" policy. Based on the study conducted, it was found that: first, the assessment pattern consists of ALK assessment in addition to AKM and AK. Where the object of evaluation is more focused on input, process and out put. In addition, the elimination of the UN, USBN is returned to the School and conducts National Assessment (AN). as for the aspects of the National Assessment include, Minimum Competency Assessment (AKM), Character Survey (SK), and Work Environment Survey (SLK). Secondly, there is a relevance between the objectives of Islamic education and the object of assessment in the elements of the Minimum Competency Assessment (AKM) Character Survey (SK).